DATA COLLECTION SYSTEM PLAYER STATISTICS ON WOMEN MAIN BASKETBALL COMPETITION (KOBANITA) - Yudhi Hari Prasetyo; Jalinas Jalinas, SKom, MM (Jurnal Sistem Informasi, 2003)
The development of sport in this country continue to be a topic of discussion by our society, along with advances in technology that makes information easily and quickly obtained. Basketball is one sport that is growing rapidly, this can be seen from the proliferation tournaments are not the least inviting sponsors and spectators. In a competition, there are data that can be processed in the field to determine the quality of one player and also a club. The author considers interesting data collection problems at the branch because of lack of attention to basketball PERBASI PB (Big Board's Basketball All-Indonesian Association) in conducting the data collection statistics, which do not have PB PERBASI concrete and measurable data to determine how far a player of quality. The data so far there is less support to find quality players because data collection is done semi-manually and that criteria is not of international standard in determining an MVP (Most Valuable Player).